2009
DOI: 10.1093/ejechocard/jen295
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of defective ultrasound transducers in use in routine clinical practice

Abstract: The high error frequency and the risk for incorrect medical decisions when using a defective transducer indicate an urgent need for increased testing of the transducers in clinical departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 9 publications
3
66
1
1
Order By: Relevance
“…Besides phantom measurements, e.g. testing systems examining the functionality of every element of the transducer can be utilized (13,14). While the new American College of Radiology (ACR) standard on monitoring the performance of real-time US equipment lists recommended image quality parameters to be checked regularly, it does not always specify what methodology should be utilized in gathering the results (11).…”
mentioning
confidence: 99%
“…Besides phantom measurements, e.g. testing systems examining the functionality of every element of the transducer can be utilized (13,14). While the new American College of Radiology (ACR) standard on monitoring the performance of real-time US equipment lists recommended image quality parameters to be checked regularly, it does not always specify what methodology should be utilized in gathering the results (11).…”
mentioning
confidence: 99%
“…This is the same type of connector that is used in the scanner, which means that this type of error can be intermittent when the transducer is connected to the scanner as well. Breaks in the cable were the second most reported defect (after delamination) by Mårtensson et al 12. Cable failures are by nature typical to sometimes be intermittent.…”
Section: Discussionmentioning
confidence: 96%
“…It is therefore subject to become defective. Not surprisingly, it has been shown that the incidence of defective transducers in clinical practice is high 12, 13, 14, 15, 16. As an example of a clinically relevant effect of defective transducers, the accuracy of Doppler measurements has been shown to be affected when several adjacent elements in the transducers are dysfunctional 17, 18…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that when ultrasonic transducers are extensively used for a long period of time image quality deteriorates [1][2][3]. The in-air reverberation test is a method for assessing changes in medical ultrasound transducer sensitivity.…”
Section: In-air Reverberation Testmentioning
confidence: 99%
“…This change in imaging performance is attributed to a number of factors which includes delamination between transducer layers, breakages in cables or components, short circuits, and weak or dead crystals [1,2]. There are number of quality assurance methods used for routinely checking transducer image quality.…”
Section: Introductionmentioning
confidence: 99%